Hierarchical control for flexible microgrid based on three-phase voltage source inverters operated in parallel. (February 2018) - Ziouani, Islam; Boukhetala, Djamel; Darcherif, Abdel-Moumen; Amghar, Bilal; El Abbassi, Ikram
Highlights: Enhancement of the universal droop control with hierarchical structure. Regardless of the output impedance of VSIs, the local demand is shared among them. This control scheme ensures the stability during the islanded mode. Seamless transition from islanded mode to grid-connected mode. Inject the scheduled power of the VSIs during the grid-connected mode. Abstract: In this paper, a hierarchical control for flexible operation of a microgrid is proposed. The structure of the hierarchical control consists of inner, primary and secondary levels. The inner control is used to regulate the output voltage of the inverter which is commonly referred as zero-level. The primary control based on the universal droop control which we improve it to handle both operation modes. It is used to share the active and reactive power accurately with regardless of the output impedance of the inverters. The secondary control compensates the deviation of the microgrid voltage caused by the primary control as well as synchronizes the microgrid voltage with the grid for a smooth transition. Thus, the microgrid can operate either in grid-connected or in islanded mode by using the same control scheme. The small-signal stability of the ameliorated universal droop control is analyzed for both modes, and other levels of control are modeled. Moreover, a technique based on meta-heuristic optimization to design the hierarchical control parameters optimally is introduced. Finally, the simulation was performed on a microgrid that has three voltage source inverters (VSIs) connected in parallel and a local nonlinear load. The results demonstrate the disturbance rejection performance and the flexibility of the proposed control scheme.